PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN NASABAH SERTA DAMPAKNYA TERHADAP LOYALITAS NASABAH (STUDI KASUS PADA BCA BIZZ KCU SEMARANG) - Dewi Setyani, 12.05.51.0010; Tjahjaningsih, Endang (Students Journal of Economic and Management, 2016)
The banking sector in recent years has rapid development. It is caused every kind of banking companies compete to retain customers who already owned, or add new prospective customers. Customer loyalty can be created through a strategy of improving the quality of services, products and increase customer satisfaction by companies to customers. The problem in this research is "The factors that influence loyalty of BCA Bizz KCU Semarangâs customers". This research examined two independent variables, quality service and quality products with customer mediation satisfaction as an intervening variable. The purpose of this research is to determine the influence of the quality of service and product quality to customer satisfaction and its impact on customer loyalty. This research was conducted by questionnaire to 100 customers of the total population of the BCA Bizz KCU Semarangâs customers as many as 1,316 customers using purposive sampling method. Then analysis to the obtained data using quantitative and qualitative analysis. Quantitative analysis includes the validity and reliability testing, test the coefficient of determination (R2), F test, hypothesis test (T test), and path analysis. Qualitative analysis is the interpretation of data obtained in the research and the results of data processing that has been carried out by giving a description and explanation. The results of this research indicate that all independent variables tested has significant and positive influence on customer loyalty through F test and T test, whereas the number R of 0.897 means 89.7% variation loyalty of BCA Bizz KCU Semarangâs customers which could be explained by the quality of service, product quality as well as customer satisfaction, and the remaining 10.3% is influenced by factors outside of this research. Keywords: Quality of Service, Product Quality, Customer Satisfaction, and Customer Loyalty.